TERSEKAT-SEKAT: MEMAHAMI HUBUNGAN ANTARRELAWAN ON-SITE RUANG BELAJAR AQIL MELALUI INTERAKSI SEHARI-HARI (Universitas Negeri Surabaya, 2023)
This study aims to determine interpersonal communication among volunteers who work directly at the secretariat of the Ruang Belajar Aqil, including verbal and nonverbal disclosures. This research is descriptive qualitative research with a phenomenological method. The paradigm of this study is constructive, where direct and detailed observations need to be made of the social actors who create and manage the world. The research data was obtained through interviews and participatory observation. The results of this study indicate that the interpersonal communication of on-site volunteers in the Ruang Belajar Aqil is ineffective. A change in attitude towards a better one, according to the definition of the related organization, has not been achieved. Openness and trust, or what can be called mutual understanding, are not present in the process of interpersonal communication in related organizations. Interpersonal communication can be saved because of non-verbal communication.